Efficient non-doped deep-blue electroluminescence devices based on unsymmetrical and highly twisted pyrene derivatives. (30th October 2017) - Wang, Zhiqiang; Zheng, Caijun; Fu, Weijun; Xu, Chen; Wu, Jiasheng; Ji, Baoming
Abstract : Pyrene derivatives with unsymmetrical and highly twisted structure appropriately confined the conjugation extent of molecules resulting in efficient deep-blue emissions. Abstract : Two novel pyrene derivatives 1-3, 5-diphenylphenyl-6-[2-(3, 5-diphenylphenyl)phenyl]pyrene (PyPP) and 1-3, 5-diphenylphenyl-6-[2-(9-phenyl-9 H -carbazol-3-yl)phenyl]pyrene (PyPC) were successfully synthesized and characterized. Both these compounds exhibit unsymmetrical and highly twisted structures, and show efficient deep-blue emissions and high thermal stabilities. The non-doped electroluminescence devices based on PyPP and PyPC exhibit stable and efficient deep-blue emissions with high color purity. The Commission Internationale de l'Éclairage (CIE) coordinate and maximum external quantum efficiency (EQE) of the device based on PyPP are (0.16, 0.07) and 2.99%, respectively. The device based on PyPC achieved a maximum EQE of 3.72% and a CIE coordinate of (0.16, 0.09).